2021
DOI: 10.1038/s41598-021-92734-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary adverse drug event data in hypertension with implications on COVID-19 morbidity

Abstract: Hypertension is a recognized comorbidity for COVID-19. The association of antihypertensive medications with outcomes in patients with hypertension is not fully described. However, angiotensin-converting enzyme 2 (ACE2), responsible for host entry of the novel coronavirus (SARS-CoV-2) leading to COVID-19, is postulated to be upregulated in patients taking angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs). Here, we evaluated the occurrence of pulmonary adverse drug even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We used VOSviewer software to analyze the association between the most productive authors and the most cited references to generate the network map and clusters visualization. Finally, we augmented qualitative text analysis using natural language processing (NLP) to investigate key characteristics and the pattern associations with nanotechnology and the top 10 cancer types [30,31]. Under the qualitative method, we mainly focus on qualitative text analysis or qualitative content analysis (e.g., thematic analysis).…”
Section: Methodsmentioning
confidence: 99%
“…We used VOSviewer software to analyze the association between the most productive authors and the most cited references to generate the network map and clusters visualization. Finally, we augmented qualitative text analysis using natural language processing (NLP) to investigate key characteristics and the pattern associations with nanotechnology and the top 10 cancer types [30,31]. Under the qualitative method, we mainly focus on qualitative text analysis or qualitative content analysis (e.g., thematic analysis).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the potential risk of drug-drug interactions is largely unknown since most studies on COVID-19 do not provide details on interactions between drugs used in the course of COVID-19 treatment and co-medications used for the management of other comorbidities in these patients 53 . Moreover, the use of some commonly used drugs in COVID patients may lead to an increased number of adverse pulmonary effects 54 . The current direction is to find suitable drugs that have a certain therapeutic effect and relatively few side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that quinapril and trandolapril were significantly different from other ACEI and ARB drug classes ( Jaberi-Douraki et al, 2021 ). Separating from its drug class was initially observed in Figure 2 when the PCA biplot was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Different quantitative therapeutic efforts in drug repurposing or repositioning combined with adverse drug event (ADE) identification have led to more efficient therapies while improving the clinical course, lowering fatality, and decreasing cost burden ( Smith and Smith, 2021 ). The previous work focused on the incidence of pulmonary ADEs associated with ACEI and ARB use in patients with hypertension and other comorbidities ( Stafford et al, 2020 ; Jaberi-Douraki et al, 2021 ). The findings indicate that specific drugs—rather than entire classes—have higher incidences of pulmonary ADEs, which may have implications for treating patients diagnosed with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation